ANALISIS PENGARUH BEBAN PAJAK TANGGUHAN DAN PERENCANAAN PAJAK TERHADAP MANAJEMEN LABA - Ria Indah Rahmawati; Salis Musta Ani; Indah Masri (ESENSI: Jurnal Manajemen Bisnis, 2021)
Earnings management is a practice that is often carried out by companies in order to improve the quality of the company in attracting investors. This study aims to analyze the effect of Deferred Tax Expense and Tax Planning with Company Size, Forest Level, and Company Growth as control variables on Earnings Management. This research was conducted on consumer goods industrial manufacturing companies listed on the Indonesia Stock Exchange in the 2018 – 2019 period. The data used in this study is based on annual financial reports obtained through the www.idx.co.id website. The number of samples taken as many as 22 companies with a research period of 2 years. The research sample was taken using purposive sampling method with the aim of obtaining samples according to the criteria. The analytical method used is panel data linear regression with the E-Views 9 for Windows analysis tool. The test results prove that the Deferred Tax Expense and Tax Planning affect earnings management in a positive direction. These results prove that earnings management practices can be detected through the amount of tax deferred and tax planning carried out by the company.